Thresholds for blood transfusion in extremely preterm infants: A review of the latest evidence from two large clinical trials - Meyer, Michael P.; O'Connor, Kristin L.; Meyer, Jill H. (Frontiers in Pediatrics, 2022)
There are two recently completed large randomised clinical trials of blood transfusions in the preterm infants most at risk of requiring them. Liberal and restrictive strategies were compared with composite primary outcome measures of death and neurodevelopmental impairment. Infants managed under restrictive guidelines fared no worse in regard to mortality and neurodevelopment in early life. The studies had remarkably similar demographics and used similar transfusion guidelines. In both, there were fewer transfusions in the restrictive arm. Nevertheless, there were large differences between the studies in regard to transfusion exposure with almost 3 times the number of transfusions per participant in the TOP study (Transfusion of Prematures). Associated with this, there were differences between the studies in various outcomes. For example, the combined primary outcome of death or neurodevelopmental impairment was more likely to occur in the TOP study and the mortality rate itself was considerably higher. Whilst the reasons for these differences are likely multifactorial, it does raise the question as to whether they could be related to the transfusions themselves? Clearly, every effort should be made to reduce exposure to transfusions and this was more successful in the ETTNO study (Effects of Transfusion Thresholds on Neurocognitive Outcomes). In this review, we look at factors which may explain these transfusion differences and the differences in outcomes, in particular neurodevelopment at age 2 yrs. In choosing which guidelines to follow, centres using liberal guidelines should be encouraged to adopt more restrictive ones. However, should centres with more restrictive guidelines change to ones similar to those in the studies? The evidence for this is less compelling, particularly given the wide range of transfusion exposure between studies. Individual centres already using restrictive guidelines should assess the validity of the findings in light of their own transfusion experience. In addition, it should be remembered that the study guidelines were pragmatic and acceptable to a large number of centres. The major focus in these guidelines was on haemoglobin levels which do not necessarily reflect tissue oxygenation. Other factors such as the level of erythropoiesis should also be taken into account before deciding whether to transfuse.